A ribonucleoprotein‐based decaplex CRISPR/Cas9 knockout strategy for CHO host engineering. (11th October 2021) - Carver, Joseph; Kern, Marie; Ko, Peggy; Greenwood‐Goodwin, Midori; Yu, X. Christopher; Duan, Dana; Tang, Danming; Misaghi, Shahram; Auslaender, Simon; Haley, Ben; Yuk, Inn H.; Shen, Amy
Abstract: Chinese hamster ovary (CHO) cell engineering based on CRISPR/Cas9 knockout (KO) technology requires the delivery of guide RNA (gRNA) and Cas9 enzyme for efficient gene targeting. With an ever‐increasing list of promising gene targets, developing, and optimizing a multiplex gene KO protocol is crucial for rapid CHO cell engineering. Here, we describe a method that can support efficient targeting and KO of up to 10 genes through sequential transfections. This method utilizes Cas9 protein to first screen multiple synthetic gRNAs per gene, followed by Sanger sequencing indel analysis, to identify effective gRNA sequences. Using sequential transfections of these potent gRNAs led to the isolation of single cell clones with the targeted deletion of all 10 genes (as confirmed by Sanger sequencing at the DNA level and mass spectrometry at the protein level). Screening 704 single cell clones yielded 6 clones in which all 10 genes were deleted through sequential transfections, demonstrating the success of this decaplex gene editing strategy. This pragmatic approach substantially reduces the time and effort required to generate multiple gene knockouts in CHO cells.